Essentials of business continuity and risk management: business impact analysis and risk assessment - Engemann, Kurt J. (Henry Stewart Talks, 2011)
Business continuity phases, Business continuity management stages, Development, Organizations and operations, Recovery time and point objectives, Critical operations, Interdependencies, Single-point-of-failure, Principles of risk management, Organizational impact, Crisis, Disruptions and disasters, Risk event chain, Controls, The steps of risk assessment, Threat identification, Outage examples, Event probability estimation, Impact criteria and estimation, Direct and indirect losses, Risk classification, measure and treatment, Developing strategies